Effects of lead poisoning in children- A narrative review (Research, Society and Development, 2021)
Objective: exposure of children to lead still poses a major health concern for public health agencies worldwide. This work aims to describe which are the symptoms most frequently associated with lead exposure in children, providing further basis to both researchers and policy makers to better guide future efforts aimed at addressing such issue. Methods: a systematized review of articles on the present topic published between June 2005 and February 2021 was carried out. Results: data described in the reviewed articles show a clear relationship between blood lead levels and hematopoietic and cognitive effects in children exposed to either low or high levels of lead. Concerning effects can be identified at blood lead levels above 4µg/dL, and the highest blood lead level reported was of 88.39 µg/dL. Conclusions: lead poisoning of children continues to be a serious public health issue worldwide, especially for those in South America, and health agencies and policy makers alike would benefit from more studies describing areas where lead exposure is high as well as describing how children have been responding to such exposure in the past years in order to better combat this issue.